$d [ b h 2 ] d t = V TPH ( t r p , b h 4 , e 5 h t ) – V DRR ( b h 2 , NADPH , b h 4 , NADP )$ (7) $d [ b h 4 ] d t = V DRR ( b h 2 , NADPH , b h 4 , NADP ) – V TPH ( t r p , b h 4 , e 5 h t )$ (8) $d [ t r p ] d t = V t r p i n ( b t r p ) – V TPH ( t r p , b h 4 , e 5 h t ) – V t r p - p o o l ( t r p , t r p – p o o l )$ (9) $d [ 5 h t p ] d t = V TPH ( t r p , b h 4 , e 5 h t ) – V AADC ( 5 h t p )$ (10) $d [ c 5 h t ] d t = V AADC ( 5 h t p ) – V MAT ( c 5 h t , v 5 h t ) + f l u o x ( t ) V SERT ( e 5 h t ) – V c 5 h t c a t a b ( c 5 h t )$ (11) $d [ v 5 h t ] d t = V MAT ( c 5 h t , v 5 h t ) – r e l e a s e ( e 5 h t ) f i r e ( t ) v 5 h t$ (12) $d [ e 5 h t ] d t = r e l e a s e ( e 5 h t ) f i r e ( t ) v 5 h t – f l u o x ( t ) V S E R T ( e 5 h t ) – V e 5 h t c a t a b ( e 5 h t ) − V r e m ( e 5 h t )$ (13) $d [ 5 h i a a ] d t = V c 5 h t c a t a b ( c 5 h t ) + V e 5 h t c a t a b ( e 5 h t ) − k h i a a c a t a b .5 h i a a$ (14) $d [ t r p − p o o l ] d t = V t r p – p o o l ( t r p , t r p − p o o l ) − k t r p − p o o l c a t a b ⋅ t r p − p o o l$ (15)